2018
DOI: 10.3390/nu10111751
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Clinical Utility of the Proposed ICD-11 and DSM-5 Diagnostic Schemes for Eating Disorders Characterized by Recurrent Binge Eating in People with a High BMI

Abstract: The aims of this paper were to compare (1) the proportion of participants diagnosed with threshold or subthreshold Bulimia Nervosa (BN) and Binge Eating Disorder (BED) (clinical utility), and (2) the severity of participants’ clinical features and mental Health-Related Quality of Life (HRQoL) (convergent validity), when diagnosed according to either the Diagnostic and Statistical Manual of Mental Disorders—5th edition (DSM-5) or the proposed International Classification of Diseases 11th edition (ICD-11) scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
2
5
1
Order By: Relevance
“…However, the prevalence of BN was the same and of OSFED-BN/BED were closely similar. This contrasts with Palavras et al (2018) who found in a clinical propulsion 14% of individuals to be diagnosed with DSM-5 BN versus 18.7% diagnosed with ICD-11 BN and 65.4% of individuals diagnosed with DSM-5 BED versus 76.6% diagnosed with ICD-11 BED. Thus, the broader criteria proposed in the ICD-11 increases the number of people with BED to a greater degree than in the DSM-5 and this was more marked in this community population.…”
Section: Discussioncontrasting
confidence: 76%
“…However, the prevalence of BN was the same and of OSFED-BN/BED were closely similar. This contrasts with Palavras et al (2018) who found in a clinical propulsion 14% of individuals to be diagnosed with DSM-5 BN versus 18.7% diagnosed with ICD-11 BN and 65.4% of individuals diagnosed with DSM-5 BED versus 76.6% diagnosed with ICD-11 BED. Thus, the broader criteria proposed in the ICD-11 increases the number of people with BED to a greater degree than in the DSM-5 and this was more marked in this community population.…”
Section: Discussioncontrasting
confidence: 76%
“…The validated EBQ can now be used in research investigations; for example, the role of potentially remedial beliefs and behaviors as indicators of obesity and eating disorder risk. Amorim Palavaras et al [18] found that the broader definition of binge eating (with emphasis on loss of control over eating rather than quantity consumed) in the ICD-11 proved of greater utility without loss of validity in a clinical population of individuals with high BMI.…”
Section: Assessment and Diagnosismentioning
confidence: 99%
“…binge eating disorder, allowing for the occurrence of subjective binge eating episodes, thus potentially increasing the clinical utility of the ICD-11 compared with the DSM-5-TR for binge eating disorder. 33,34 ARFID is characterised by the avoidance of and aversion to food and eating. 1,2 Notably, this restriction is not the result of a body image disturbance but is due to anxiety or a heightened sensitivity to the sensory aspects of food.…”
Section: Discussionmentioning
confidence: 99%
“…The DSM‐5‐TR and ICD‐11 differ in their criteria for binge eating disorder, with the DSM‐5‐TR requiring three additional descriptors 1,2 . The broader ICD‐11 criteria appear more congruent with lived experience reports of binge eating disorder, allowing for the occurrence of subjective binge eating episodes, thus potentially increasing the clinical utility of the ICD‐11 compared with the DSM‐5‐TR for binge eating disorder 33,34 …”
Section: Diagnosis and Classificationmentioning
confidence: 99%